WORDS THAT PROVOKED DISHONESTIES: The Requesting Priests and the Recolhimento de Nossa Senhora da Conceicao de Macaoebas - Silva, Sabrina Alves da [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2024)
The inquisitorial offense of solicitation occurred when a confessor, at the place of confession, sexually or lovingly harassed the penitents. The Church and the Inquisition treated the Sacrament of Penance with great diligence, assigning it part of the responsibility for inculcating virtuous models of behavior valued by the Tridentine reforms. Solicitation was understood as a means of tainting the sacrament of confession, thus falling under inquisitorial jurisdiction. Two priests, prosecuted and sentenced for solicitation, committed the crime at the Recolhimento de Nossa Senhora da Conceicao de Maca oe bas, an important institution composed of retirees, pensioners, and schoolgirls, and a place for elite women. Unlike convents, this gathering accepted blacks, Indians, mestizos, and illegitimate daughters.
Keywords: Request; Priests; Inquisition; Gathered